2021
DOI: 10.5603/cj.a2020.0127
|View full text |Cite
|
Sign up to set email alerts
|

Small vessel coronary artery disease: How small can we go with myocardial revascularization?

Abstract: The issue of small coronary artery atherosclerosis represents an intriguing aspect of coronary artery disease, which is related with higher rates of peri-and post-procedural complications and impaired long-term outcome. This problem is further complicated by the unclear definition of small coronary vessel. Recent randomized controlled trials have provided new data on possible novel interventional treatment of small coronary vessels with drug-coated balloons instead of traditional new-generation drug-eluting st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 76 publications
(104 reference statements)
0
12
1
Order By: Relevance
“…Although previous data provided evidence for a higher rate of restenosis in patients with SVD subject to PCI, our study did not provide data to support it [5]. While restenosis was more common in patients with SVD, the difference did not reach statistical significance.…”
Section: Discussioncontrasting
confidence: 95%
“…Although previous data provided evidence for a higher rate of restenosis in patients with SVD subject to PCI, our study did not provide data to support it [5]. While restenosis was more common in patients with SVD, the difference did not reach statistical significance.…”
Section: Discussioncontrasting
confidence: 95%
“…Coronary vessel diameter has a continuous inverse relationship with procedural complexity and the incidence of cardiac events [4,14,15]. Correspondingly, the definitions of what constitute a small vessel is arbitrary, varies between studies and has evolved over time [6]. Initially, in the early days of bare metal stents, vessels ≤ 2.9 mm in lumen diameter were considered small [16].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of small vessel treatment among patients undergoing a percutaneous coronary intervention (PCI) has been reported to be around 35-50% of the cases [1][2][3][4]. For the interventional cardiologist, small vessel PCI constitute a technical challenge as small vessels are more distally located in the coronary system with frequently a diffuse distribution of the atherosclerotic narrowing's rather than a discrete lesion [5,6]. Moreover, small vessel disease is associated with an increased risk for a cardiac event, including Koki Shishido is a first author.…”
Section: Introductionmentioning
confidence: 99%
“…Coronary artery SVD accounts for 30% of patients needing interventional therapy and is more common in women or the elderly and patients with diabetes or kidney disease (45). The small vessel diameter makes it challenging for stent implantation (46). Moreover, previous studies have shown that small vessel diameter is the strongest inducer of restenosis among all clinical factors (47), which leads to the high probability of ISR in SVD after DES treatment.…”
Section: Application Of Dcb In Small Vessel Diseasementioning
confidence: 99%